ANALISIS PENGARUH KUALITAS INFORMASI, KUALITAS SISTEM, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA SOFTWARE ACCURATE DI KOTA SEMARANG - Sidiq, Fajar; Adhi, Daniel Kartika (STIE PENA, 2025)
Accurate is an accounting software used to assist the bookkeeping and financial reporting process in business. This Accurate software is specifically designed to assist small to medium businesses in managing finances, such as purchases, sales, inventory, and tax reports. This study aims to determine the effect of Information Quality, System Quality, and Service Quality on Accurate Software User Satisfaction in Semarang City. This type of research uses a quantitative approach. The population in this study were Accurate Software users in Semarang City. The sample used was 98 respondents, using purposive sampling with a questionnaire data collection method. The analysis method in this study is multiple linear regression analysis with validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test, F test and determination coefficient test. Data processing uses SPSS 25 for Windows software. The results of this study indicate that Information Quality has no significant effect on User Satisfaction of Accounting Information Systems with a significance level of 0.103 > 0.05, while t count 1.646 < t table 1.66123. System Quality has a positive and insignificant effect on User Satisfaction of Accounting Information Systems with a significance level of 0.091 > 0.05, while t count 1.709 > t table 1.66123. Service Quality has a significant positive effect on User Satisfaction of Accounting Information Systems with a significance level of 0.000 < 0.05, while t count 3.798 > t table 1.66123. Information Quality, System Quality, and Service Quality simultaneously have a significant positive effect on User Satisfaction of Accounting Information Systems with a significance level of 0.00 < 0.05, while F count 69.966 > F table 2.70. Keywords: Information Quality, System Quality, Service Quality, User Satisfaction of Accounting Information Systems